Working Time and Employment under Uncertainty - Yu-Fu Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2002)
The standard literature on working time has modelled the decisions of firms in a deterministic framework in which firms can choose between employment and overtime (given mandated standard hours). Contrary to this approach, we consider the impact of uncertainty and real options on the decision of working time, i.e. we examines the determinants of employment and hours in a stochastic framework. We conclude the theoretical analysis with a number of simulation exercises to illustrate the working of the model.
Keywords: 330; real options; uncertainty; working time; employment; labor demand